The Relationship Between Coping and Stress Levels in Students from The Class of 2020 at The Faculty of Medicine, Palangka Raya University, During Their Thesis Preparation - Netanya Gloria; Natalia Sri Martani; Syamsul Arifin; Helena Jelita; Astri Widiarti (Jurnal Psikiatri Surabaya, 2024)
Introduction: Academic stress is prevalent among final-year students, with thesis preparation being a significant source of this stress. Coping are essential as they effectively represent the body’s conscious adaptive responses to reduce stress through self-adaptation. This research determines the relationship between coping and stress levels in students from the class of 2020 at the Faculty of Medicine, Palangka Raya University, during their thesis preparation. Methods: The study employs a quantitative analytical observational design with a cross-sectional approach. Simple random sampling was utilized for participant selection. The research instruments comprised coping questionnaires and the Perceived Stress Scale (PSS-10). Data were analyzed using Charles Spearman’s correlation analysis with a confidence interval of 95%. Results: Out of all 96 respondents, 49 individuals (51%) had good coping skills, and 80 individuals (83.3%) experienced moderate stress levels. Notably, among the 49 participants exhibiting good coping, a majority (42 individuals or 85.71%) experienced moderate stress levels. The Charles Spearman test findings revealed a significant value of 0,013 (p < 0.05) with a weak correlation and the opposite direction (r = -0.252). Conclusion: There is a significant relationship between coping and stress levels in students from the class of 2020 at the Faculty of Medicine, Palangka Raya University, during their thesis preparation.